The da'wah methods used by selected islamic organisations in Selangor and Kuala Lumpur countering atheism - Nur Afifah Abdul Razak (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This study seeks to highlight two important points. Firstly, it intends to ascertain the ideological formulation of atheism and atheists. Precisely, this research aims to understand what atheism is and who is an atheist. The elaboration includes primary and secondary definitions of atheism and atheists as well as the alternative ideologies to atheism. A comprehensive discussion on the typologies, psychological and sociological conditions of an atheist are also included in the study. Next, the research examines the structure of the Islamic constitutional system, clarifying the position and the jurisdiction of the Islamic organisations in Malaysia. The three selected organisations are the ʻAqidah Consultation Unit of Mufti of Federal Territories, the Advisory Service Unit of Selangor Mufti Department and the Modern Daie Society Malaysia. Secondly, the study seeks to analyse the daʻwah methods used by the organisations in dealing with the cases of atheism. The study indicates that the daʻwah methods used by the selected organisations are in accordance with the main principles highlighted by the Qur'an. The research also gathers response of the selected organisations in observing the phenomenon of atheism in Malaysia. This is a qualitative study in nature. It adopts textual analysis in gaining the works of literature related to the atheism and atheists. Meanwhile, data analysis was applied in doing a comparison on the daʻwah modules used by the selected organisations. A series of interviews were also conducted to obtain the data and the responses from the officers in-charge at the organisations.